PENGARUH PROMOSI, KUALITAS PELAYANAN, MOTIVASI DAN PERSEPSI TERHADAP KEPUTUSAN NASABAH MEMILIH PRODUK TABUNGAN EMAS DI PEGADAIAN SYARIAH PEKALONGAN: Dibuat oleh Novita Mega Mentari, Fadli Hudaya, Yohani - Yohani, Y; Mega mentari, Novita; Hudaya, Fadli (Neraca, 2021)
This study aims to test the effect of promotion, quality of service, motivation, and perception both partially and simultaneously on the decision of customers to choose gold savings products at Pegadaian Syariah Pekalongan. This study is quantitive research. The population was gold savings customers at Pegadaian Syariah Pekalongan. This research used purposive sampling technique, data was collected by distribute questionnaire to 100 respondents. After conducting the study, the researchers obtained data calculated using the Slovin formula SPSS version 24.0 was used to analyze data. The data analysis techniques used are multiple linier regression equation analysis, T Test, F Test and determination coefficient analysis. The results of this study showed that: partially promotion, quality of service, motivation, and perception have a significant effect on the decision of the customer choosing a gold savings product, simultaneously promotion, quality of service, motivation and perception significantlye effect the decision of the customer choosing a gold savings product. The resulting coefficient of determination is 0,476 or 47,6%. Keywords: Promotion, Quality of Service, Motivation, Perception and Customer Decision